Bilateral Supratentorial Subdural Hematomas after Craniotomy for Posterior Fossa Tumor Removal - Solomou, Aikaterini; Kraniotis, Pantelis; Bonanos, George; Constantoyannis, Constantine (Journal of Neurological Surgery Reports, 2018)
A 69-year-old man was admitted to the emergency department with headache and dizziness. He was submitted to brain computed tomography (CT) which showed a tumor in the right cerebellar hemisphere, findings which were subsequently confirmed with magnetic resonance imaging (MRI). He underwent a paramedian suboccipital craniotomy for removal of the mass. Histology confirmed the presence of a hemangiopericytoma. The patient was discharged 5 days postoperatively with improvement in his symptoms. Fifteen days later, he presented with gait difficulties. Clinical examination revealed positive Mingazzini sign on his left side. He was submitted to brain MRI which revealed bilateral subdural hematomas on late subacute stage with mass effect and midline shift caused by the largest on the right. The patient underwent burr hole evacuation of the right subdural hematoma. The postoperative CT showed evacuation of the right chronic subdural hematoma. Two days postoperatively, the patient's symptoms improved.
Keywords: posterior fossa tumor; hemangiopericytoma; chronic subdural hematoma